2004
DOI: 10.1074/jbc.m312533200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NADH-linked L-Xylulose Reductase in the L-Arabinose Catabolic Pathway of Yeast

Abstract: An NADH-dependent L-xylulose reductase and the corresponding gene were identified from the yeast Ambrosiozyma monospora. The enzyme is part of the yeast pathway for L-arabinose catabolism. A fungal pathway for L-arabinose utilization has been described previously for molds. In this pathway L-arabinose is sequentially converted to L-arabinitol, L-xylulose, xylitol, and D-xylulose and enters the pentose phosphate pathway as D-xylulose 5-phosphate. In molds the reductions are NADPH-linked, and the oxidations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 28 publications
5
65
0
2
Order By: Relevance
“…This pathway consists of two NAD + -linked oxidations and two NADPH-linked reductions, resulting in a redox cofactor imbalance under anaerobic conditions (Dien et al 1996). In contrast to the strictly NADP(H)-dependent L-xylulose reductase described for the molds P. chrysogenum (Chiang and Knight 1960), A. niger (Witteveen et al 1994), and Trichoderma reesei (Richard et al 2002), the L-xylulose reductase of the yeast Ambrosiozyma monospora has been reported to be strictly NADH-dependent (Verho et al 2004). It is unknown whether this is a general characteristic of this enzyme in L-arabinose-metabolizing yeasts.…”
Section: L-arabinose Fermentation By S Cerevisiaementioning
confidence: 88%
See 1 more Smart Citation
“…This pathway consists of two NAD + -linked oxidations and two NADPH-linked reductions, resulting in a redox cofactor imbalance under anaerobic conditions (Dien et al 1996). In contrast to the strictly NADP(H)-dependent L-xylulose reductase described for the molds P. chrysogenum (Chiang and Knight 1960), A. niger (Witteveen et al 1994), and Trichoderma reesei (Richard et al 2002), the L-xylulose reductase of the yeast Ambrosiozyma monospora has been reported to be strictly NADH-dependent (Verho et al 2004). It is unknown whether this is a general characteristic of this enzyme in L-arabinose-metabolizing yeasts.…”
Section: L-arabinose Fermentation By S Cerevisiaementioning
confidence: 88%
“…Another way that has been proposed to ameliorate problems with cofactor imbalances is expression of the aldose reductase gene from Pi. stipitis (Rizzi et al 1988) that also accepts NADH as cofactor, or the gene encoding NADH-dependent L-xylulose reductase (ALX1) from Ambrosiozyma monospora (Verho et al 2004). …”
Section: L-arabinose Fermentation By S Cerevisiaementioning
confidence: 99%
“…[1][2][3][4][5][6][7] Erwinia uredovora (later renamed Pantoea ananatis) is the only bacterium known to have an activity related to L-xylulose formation from xylitol. Many studies have been conducted on the mechanisms and properties of the enzyme in this organism.…”
Section: L-xylulosementioning
confidence: 99%
“…This result showed the size to be comparable with related enzymes from other sources, which appeare to have approximate sizes of 26-40 kDa on SDS-PAGE analysis. 2,3,6,11,16) We also constructed C-terminal His-tagged XDH to facilitate purification, but XDH activity was significantly lower (data not shown). Hence the non-Histagged enzyme was used throughout this study.…”
Section: Mass Production and Purification Of The Recombinant Xdhmentioning
confidence: 99%
“…The D-xylulose 5-phosphate is then further metabolized in the pentose-phosphate pathway. In a recently characterized fungal pathway (3)(4)(5), L-arabinose is also converted to D-xylulose 5-phosphate but through different intermediates by two reductases, two dehydrogenases, and a kinase. In the hypothetical pathway(s) involving nonphosphorylated intermediates in bacteria ( Fig.…”
mentioning
confidence: 99%